Modeling and design of a current mode control boost converter - Yao, Hong, author; Collins, George J., advisor; Chen, Tom W., committee member; Suryanarayanan, Siddharth, committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2012)
The boost or step up converter produces an undesirable Right-Half Plane Zero (RHPZ) in the small signal analysis of the "Duty Cycle Control to Output Voltage" transfer function. It is well documented that the boost converter has the reputation of low-performance and stability is complicated due to the RHPZ which makes Voltage Mode Control (VMC) very hard to implement. Even when Current Mode Control (CMC) is applied in the topology of converters operating in Continuous Conduction Mode (CCM), the current feedback loop becomes unstable if the duty cycle exceeds 0.5---the instability is known as Subharmonic Oscillation.

This research presents the theoretical analysis of the origin of the RHPZ and the modeling of a current mode control boost converter operating in continuous conduction mode. It details how to properly design both the control loop and the compensation loop to maintain the stability of the current-mode regulator. The simulation results and experimental results are given and contrasted based on a 3.5V-5.5V DC input, 12V DC output, and 1.3MHz switch frequency boost converter design.
Keywords: boost; right half plane zero; current mode control; converter